2017
DOI: 10.1002/cphc.201700029
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Surface of γ‐Al2O3with Y2Sn2O7Pyrochlore: Monolayer Dispersion Behaviour of Composite Oxides

Abstract: To investigate the dispersion behaviour of composite oxides on supports, and to obtain better supports for Pd for CO oxidation, a series of Y Sn O /Al O composite oxides with different Y Sn O loadings were prepared by a deposition-precipitation method. XRD and X-ray photoelectron spectroscopic extrapolation methods revealed that, similar to single-component metal oxides, composite oxides can also disperse spontaneously on support surfaces to form a monolayer with a certain capacity. The monolayer dispersion ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, they have been investigated as functional materials for various applications such as magnetic, electrical, and optical materials. The investigations on their catalytic properties are much less documented. Our former studies have demonstrated that A 2 B 2 O 7 compounds with different A- or/and B-site compositions displayed very good performance for several high-temperature reactions, including methane reforming and OCM reaction. It has been substantiated that an effective OCM catalyst usually possesses surface electrophilic oxygen sites and also has certain surface alkalinity. ,,, A typical A 2 B 2 O 7 compound containing a trivalent rare-earth A-site can provide surface alkalinity, which matches mostly the requirement of a good OCM catalyst, together with its mobile oxygen species. Therefore, our former work has testified that a La 2 Ce 2 O 7 catalyst displays very good performance for OCM reaction, especially in the low-temperature region .…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, they have been investigated as functional materials for various applications such as magnetic, electrical, and optical materials. The investigations on their catalytic properties are much less documented. Our former studies have demonstrated that A 2 B 2 O 7 compounds with different A- or/and B-site compositions displayed very good performance for several high-temperature reactions, including methane reforming and OCM reaction. It has been substantiated that an effective OCM catalyst usually possesses surface electrophilic oxygen sites and also has certain surface alkalinity. ,,, A typical A 2 B 2 O 7 compound containing a trivalent rare-earth A-site can provide surface alkalinity, which matches mostly the requirement of a good OCM catalyst, together with its mobile oxygen species. Therefore, our former work has testified that a La 2 Ce 2 O 7 catalyst displays very good performance for OCM reaction, especially in the low-temperature region .…”
Section: Introductionmentioning
confidence: 95%
“…2a and b), all Ca 2+ cations were incorporated into the lattice structure of CeO 2 , thereby eluding detection through XRD analysis. 43,44…”
Section: Resultsmentioning
confidence: 99%
“…According to the monolayer dispersion thresholds theory, [13] the characteristics of active components will not appear in the XRD pattern when loads of active components are low; when loads of active components exceed the monolayer dispersion threshold, obvious diffraction peaks of active components will appear. Based on XRD patterns, the extrapolation can be used to determine the monolayer dispersion threshold of metal oxides on the carrier [14] . ATP was taken as the internal standard, the ratio of the peak intensity of Fe 2 O 3 and the peak intensity of ATP was plotted, and the results were shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Based on XRD patterns, the extrapolation can be used to determine the monolayer dispersion threshold of metal oxides on the carrier. [14] ATP was taken as the internal standard, the ratio of the peak intensity of Fe 2 O 3 and the peak intensity of ATP was plotted, and the results were shown in Figure 2. The fitted linear equation was y = 215.25x-61.89, the point where the line intersects the X-axis was the inflection point, which indicated that the crystal phase of Fe 2 O 3 just began to…”
Section: Xrd Spectrummentioning
confidence: 99%